Chemical Castration as an Action Sanctions in Legal Perspectives and Bioethics - Akhmad, Syaefudin Ali; Harahap, Zairin; Syarwani, -; Velayati, Faris; Widati, Rohai; Anggara, BayuArif; Arofah, Berlian Siti (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: The application of chemical castration sanctions is a form of solution issued by the Indonesia Government through the Law No. 17 of 2016 regarding Child Protection on the rampant cases of child sexual abuse. However, the imposition of sanctions is considered still many shortages in it. Starting from the element of uncertainty period of implementation, the negative side effects on the body, to the procedure and technical implementation of the castration actions contained in the article. Objective: The objective of this research is known as Chemical Castration Actions of sexual violence in the review of the perspective of the enforcement law, criminal law, human rights and bioethics. Methods: The authors useds qualitative research methods with descriptive and analytical research. The sources of data are based on the information contained in the literatures bibliography and based on the interviews result. Results: The result of this study shows that chemical castration from a criminal law perspective cannot be categorized as an action sanction. From the perspective of human rights law, the right to be free from condescending punishment is an absolute right which cannot be limited at all. In the bioethics perspective, chemical castration has violated the four principles of medical ethics/bioethics. Conclusion: Chemical castration cannot be claimedaction sanction of law because it violates theprinciples of bioethics whichin resulthumiliates the dignity of medical doctor profession. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 194-201